Case Report on Acute Lymphatic Leukemia - Nilam Raut1 , Archana Mourya2 , Manoj Patil3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Leukemia are the most common cancer in children, the malignant neoplasms are the cancerof the blood or bone marrow produce blood cells. Leukemia can happens when there is a problem with theproduction of blood cells. About 30 to 40 percentage of childhood malignancies include leukemia. There ishigher proportion of T- cells. Linkage. Acute lymphocytic leukemia ALL.Case Presentation: The female patient 6yr old who was apparently admitted in AVBRH on date 16/09/2019.Patient has fever since 1 month of continuous fever spike with high grade fever, swelling over neck since onemonth and pain in the leg. Patient was diagnosed with Acute lymphatic leukemia one year back, was broughthere with complaint of one complaint of one month of continuous fever, they checked for the complaint intwo hospitals of Yawatmal, they referred to AVBRH for further management.Investigations: Complete blood count, history and physical examination, complete blood count anddifferential count, peripheral smear examination and platelets count, bone marrow aspiration and Patientdoesn’t have surgical history. Patient was treated with tab prednisolone, Induction therapy,chemotherapyNursing management: patient care was given according to patient complaint, Keep patient safe from falls atrisk of weakness or paralysis. Provide pain management, protection from infection, check lab reports,Conclusion: Patient was admitted to hospital for further treatment of acute lymphatic leukemia and he wasadmitted in AVBRH and got treatment and now the patient condition is satisfactory.